PP.33.19: IT IS MILD-OBESITY A CARDIOVASCULAR PROGNOSTIC MARKER INDEED?. (June 2015) - Hermida, A.; Lopez, J.E.; Alende, M.J.; Calvo, G.; Rodriguez, I.; Lado, J.L.; Calvo, C.
Abstract : Objective: It has been recently reported that overweight (BMI: 25–30 kg/m2) associates to lower any cause-mortality whereas mild obesity (BMI: 30–35 kg/m2) does not associate to higher mortality when compared to normal-weight. The aim of this study was to assess subclinical target organ damage prevalence and cardiovascular prognostic value of mild-obesity in a cohort of hypertensive subjects. Design and method: We designed a retrospective cohort study. The study population included 381 hypertensive patients with BMI < 35, they all underwent a complete annual medical examination from January 2011 to December 2014, including 48-hours blood pressure monitoring (ABPM) in order to diagnose those with WC effect. Following examinations were held: carotid artery ultrasound with intima/media thickness (IMT), carotid femoral PWV by Sphygmocor At Cor® and oscillometric measurement of ABI. Blood and urine samples were used for the determination of glomerular filtration rate by MDRD equation (GFR) and Sokolow-Lyon criteria for left ventricular hypertrophy (LVH). Primary endpoint was the combination of fatal/non-fatal coronary heart disease or fatal/non-fatal stroke, or peripheral revascularization. All events were confirmed on the basis of medical records. Results: The overall prevalence rates of normal-weight (mean age: 48.8 years) and mild-obesity (mean age: 58.4 years) were 56.7 and 43.3%, respectively. We didn[Combining Acute Accent]t find difference on gender but on waist perimeter, office pulse pressure, 48hour-dyastolic BP and nocturnal blood pressure falling. Regarding TOD prevalence, GFR was higher on normal-weight subjects (84.3 Vs 78.9 ml/min/1.72 m2), PWV lower (8.7 Vs 10.4 m/sec) and also lower IMT (0.76 Vs 0.85 mms). So TOD prevalence among normal weight hypertensive subjects was 27.3% (Vs 51.5%). A total of 13 cardiovascular events were identified: six on normal weight hypertensive subjects (5.2%) and seven on mild-obesity subjects (4.5%). Multivariate analysis didn't demonstrate higher CV risk on mild-obesity hypertensive patients. Conclusions: Comparing both hypertensive groups, even taking into account higher mean age on mild-obesity group, we did not find differences on CV events incidence rate. Nevertheless, we found higher prevalence of impaired nocturnal BP falling and also subclinical TOD prevalence when mild-obesity.